Strategi Bisnis Dalam Menentukan Kinerja Keuangan Perusahaan Properti Di Indonesia - Eni Suharti; Dhea Zatira; Hamdani; Yogy Hendarji (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
The purpose of this research is to look at the effects of business risk (DOL), growth strategy (SG) and capital structure (DER) on the performance of manufacturing companies in the property sub-sector listed on the Indonesia Stock Exchange in 2016-2020. This study uses a quantitative approach, with a population of 28 property sub-sector companies that are still listed on the Indonesia Stock Exchange for the period 2016 to 2020 and a sample of 22 companies where the sampling technique uses purposive sampling. The data analysis technique used is panel data regression analysis with the help of the Eviews 9 program. The results show that partially capital structure (DER) has no effect on company performance, business risk variable (DOL) has a positive and significant effect on company performance and for strategy variables growth (SG) partially has a positive and significant effect on company performance. Simultaneously business risk (DOL), growth strategy (SG) and capital structure (DER) have a positive and significant effect on company performance in the 2016-2020 period.